Annual Research Review: Defining and treating pediatric treatment‐resistant depression. (4th February 2020) - Dwyer, Jennifer B.; Stringaris, Argyris; Brent, David A.; Bloch, Michael H.
Abstract : Background: Adolescent major depressive disorder (MDD) is a significant health problem, associated with substantial morbidity, cost, and mortality. Depression is a significant risk factor for suicide, which is now the second leading cause of death in young people. Up to twenty per cent of adolescents will experience MDD before adulthood, and while a substantial proportion will improve with standard‐of‐care treatments (psychotherapy and medication), roughly one third will not. Methods: Here, we have reviewed the literature in order to discuss the concept of treatment‐resistant depression (TRD) in adolescence, examine risk factors, diagnostic difficulties, and challenges in evaluating symptom improvement, and providing guidance on how to define adequate medication and psychotherapy treatment trials. Results: We propose a staging model for adolescent TRD and review the treatment literature. The evidence base for first‐ and second‐line treatments primarily derives from four large pediatric clinical trials (TADS, TORDIA, ADAPT, and IMPACT). After two medications and a trial of evidence‐based psychotherapy have failed to alleviate depressive symptoms, the evidence becomes quite thin for subsequent treatments. Here, we review the evidence for the effectiveness of medication switches, medication augmentation, psychotherapy augmentation, and interventional treatments (i.e., transcranial magnetic stimulation, electroconvulsive therapy, and ketamine) for adolescent TRD. Comparisons are drawn to the adult TRD literature, and areas for future pediatric depression research are highlighted. Conclusions: As evidence is limited for treatments in this population, a careful consideration of the known risks and side effects of escalated treatments (e.g., mood stabilizers and atypical antipsychotics) is warranted and weighed against potential, but often untested, benefits. Abstract : Read the Commentary on this article at doi: 10.1111/jcpp.13207